Germicidal effect of hydrogen peroxide nano-silver ion composite disinfectant and its effect on the microbial community of shrimp intestine and rearing water - Hou, Danqing; Lin, Zexu; Zhou, Jianing; Xue, Yuan; Sun, Chengbo (Frontiers in Marine Science, 2023)
In this study, the inhibitory effect of different doses of hydrogen peroxide nano-silver ion composite disinfectant (HPS) on DIV1 and bacteria was analyzed, and the antibacterial activity of three disinfectants, HPS, potassium monopersulfate (KMPS) and calcium hypochlorite (Ca(ClO)2), was compared. In addition, 16S rDNA amplification sequencing technology was used to analyze the effects of these three disinfectants on the intestinal microflora of Litopenaeus vannamei and the structure and composition of water microflora. The results showed that HPS did not positively affect the survival rate of prawns infected with DIV1, which needs to be verified in future studies. In the experimental design range, the higher the dosage of HPS, the more obvious the killing effect on the number of Vibrio and total bacteria in rearing water, and the two showed a negative correlation. 5,104 OTUs were obtained based on 16S rDNA high-throughput sequencing, of which 3,012 (59.01%) and 1,475 (28.90%) OUTs were annotated at the phylum and genus levels, respectively. Proteobacteria, Firmicutes, Actinobacteriota, Bacteroidetes, and Cyanobacteria dominated the water samples at the phylum level. At the genus level, the dominant bacterial genera in the intestinal bacterial community of shrimp were Photobacterium, Vibrio, and Ruegeria. The most dominant bacteria genera in water samples were Vibrio, Ruegeria, Pseudoalteromonas, and Nautella. In the water samples, the composition and structure of the Ca(ClO)2 microbial community were relatively simple, and the species richness and diversity of Ca(ClO)2 were significantly lower than those of HPS and KMPS disinfectant groups at 12 h and 24 h (p < 0.05). In terms of inhibiting the diversity and richness of the microbial community, Ca(ClO)2 had a significant effect (p < 0.05), but the intestinal microbial community diversity of shrimp treated with HPS was higher than that of the other two groups. It is worth noting that, compared with the three disinfectants, HPS has the strongest killing effect on Vibrio and total bacteria, and has a certain positive significance for maintaining the stable state of the microbial community. This study provides a scientific basis for applying HPS in aquaculture and broadens the application range of HPS.